The Georgia O'Keeffe Museum - Hassrick, Peter H.; Messinger, Lisa Mintz; Novak, Barbara; Rose, Barbara; Georgia O'Keeffe Museum. Research Center (New York : Harry N. Abrams in association with the Georgia O'Keefe Museum, 1997)
"Georgia O'Keeffe (1887-1986), a pioneer of modernism, was unlike most of her contemporaries in that all her training and much of her subject matter were purely American. Still vigorously productive in her nineties, O'Keeffe always responded to the new in her own unique fashion. In this volume, eighty-six works from every period of her life, many never before published, are reproduced in large scale and in full color. Several are shown in lavish gatefolds." "More than a dozen photographs of the artist, including a number taken by Alfred Stieglitz, document the various stages of her life. A bibliography and full index add to the scholarly value of this handsome volume."--Jacket.
Foreword / Anne W. Marion -- Acknowledgments / Peter H. Hassrick -- Introduction: Georgia O'Keeffe and the American Dream / Mark Stevens -- Georgia O'Keeffe: Painting Her Life / Lisa Mintz Messinger -- Georgia O'Keeffe and American Intellectual and Visual Traditions / Barbara Novak -- O'Keeffe's Originality / Barbara Rose -- Chronology / Charles C. Eldredge.
Includes bibliographical references and index.
Keywords: O'Keeffe, Georgia, -- 1887-1986 -- Catalogs; Georgia O'Keeffe Museum -- Catalogs; Art -- New Mexico -- Santa Fe -- Catalogs